The Role of Tobacco Excise Revenue Sharing Funds (DBHCHT) in Reducing Tax Evasion - Tjipto Aji Sudarso; Sartika Djamaluddin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the relationship between the allocation of DBHCHT for law enforcement and tax evasion efforts, as reflected by the number of illegal cigarette seizures, during the 2021–2023 period using a panel regression model. The research employs a Random Effects Panel Regression model with the Generalized Least Squares (GLS) estimation method. The analysis results indicate that DBHCHT significantly contributes to reducing tax evasion efforts through its positive association with the number of illegal cigarette seizures. Regions receiving relatively larger DBHCHT allocations demonstrate a greater impact in curbing tax evasion attempts. Therefore, the central government should reassess the allocation of DBHCHT for law enforcement and optimize its utilization at the local government level to strengthen oversight capacity in combating the circulation of illegal cigarettes.